Flexicurity and Job Reallocation - Christian Keuschnigg; Thomas Davoine (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper considers the role of flexicurity when jobs must be reallocated from a declining, traditional sector to a skill intensive expanding sector. Workers initially decide whether to acquire qualifications for skill-intensive tasks or to accept a less demanding traditional job. Unemployment arises from job separation in the declining sector and difficulties in retraining for new employment in the expanding sector. The paper derives an optimal welfare policy which combines the design of the tax schedule with three pillars of `flexicurity'. The optimal policy includes (i) a progressive wage tax schedule; (ii) a wage subsidy to re-employed workers; (iii) unemployment insurance; (iv) moderate job protection; and (v) active labor market policy to facilitate job reallocation.
Keywords: H21; J64; J65; 330